Conceptual models for technology adoption by small scale farmers - Ajayi, O.; Nokoe, S. (2000)
Acceleration of agricultural production rates to meet the needs of an ever-growing population remains a central issue today as ever in World agriculture. Various national and international agricultural research centres around the world have invested much efforts in developing new technologies with great potentials for better yield than existing ones, but the level of farmers' adoption of these, which is crucial to the much needed increased production rates have been quite low. Interestingly, studies have shown that technology adoption is not an "event" but a "process" which is dynamic and influenced by some important socio-economic factors. This study, develop models that relates technology adoption rate to these co-determining factors. In general terms, the model should give a very quick knowledge of expected adoption rate, while its estimated parameters will give hints on methods for improved performance.